Islamisasi Kerajaan Kutai Kertanegara Abad Ke-16: Studi Historiografi Naskah Arab Melayu Salasilah Kutai - Muhammad Sarip; Nabila Nandini (Yupa: Historical Studies Journal, 2021)
The event of Islamization in Kutai Kertanegara Monarchy needs to be reviewed on the basis of verified primary sources. This study aims to analyze the validity of Surat Salasilah Raja dalam Negeri Kutai Kertanegara Malay-Arabic script, as a source of traditional historiography. The script describes the process of Islamization in the Monarchy of Kutai Kertanegara whence it begins as mythological texts then written as historical narratives. With historical research methods, the main source of this research is the book of Letters of Salasilah Raja in Kutai Kertanegara in Arabic Malay script by Khatib Muhammad Thahir which was completed in 1849. The results of the study show that, with strict verification, Salasilah Kutai is a valid historical source. The process of Islamization in the Kutai Kertanegara Monarchy took place through the role of a preacher named Tuan Tunggang Parangan who carried out an egalitarian dialectic to Raja Makota, in 1575.